(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2018)
The present work is concerned with studying the synthesis and characterization of hybrid aluminum bronze matrix strengthened with nano-aluminum oxide particles (n-Al2O3), and carbon nano tubes (CNTs). The selected matrix composite was successfully incorporated with different weighted percentages of CNTs (i.e. 1.0 and 2.0 wt.%) and/or n-Al2O3 (i.e. 1.0 and 2.0 wt.%) by sintering process. From the microstructure analysis, n- Al2O3 particles was dispersed uniformly and holding over the surface of aluminum bronze. Furthermore, some agglomeration was found due to reinforced CNTs into aluminum bronze matrix. From hardness tests, it was found that incorporated n- Al2O3 and CNTs into matrix increased the hardness of composites to be equal 230 HV, which is around 2.3 times higher than that of an aluminum bronze matrix. Moreover, the wear loss of CNTs - Al2O3/aluminum bronze composites diminished because of the impact of homogeneous circulation of CNTs in aluminum bronze and low corrosion coef?cient of uncovered CNTs on the well-used surface. Notable from the results, the electrical resistivity of the hybrid composites are lower than the matrix. Hopefully, the findings are expected to provide profound knowledge and further reference towards the studied composites of the miniaturised electronic package